Chemical Field Theory: The Inverse Density Problem of Electronegativity and Chemical Hardness for Chemical Bond - Putz, Mihai V. (Current Physical Chemistry, 2017)
The anharmonic chemical field potential, V (∅,χ ,η), is expressed in terms of the electrostatic potential, ∅, the electronegativity, χ, and the chemical hardness, η, density functionals, as they relate the electron density functional, ρ, and chemical bond formation by quantum field/operators [observable/measurable quantities (physical observables)].
Keywords: Feynman-Kleinert path integral